eCM 2011
DOI: 10.22203/ecm.v022a26
|View full text |Cite
|
Sign up to set email alerts
|

Directed migration of human bone marrow mesenchymal stem cells in a physiological direct current electric field

Abstract: At sites of bone fracture, naturally-occurring electric fi elds (EFs) exist during healing and may guide cell migration. In this study, we investigated whether EFs could direct the migration of bone marrow mesenchymal stem cells (BM-MSCs), which are known to be key players in bone formation. Human BM-MSCs were cultured in direct current EFs of 10 to 600 mV/mm. Using time-lapse microscopy, we demonstrated that an EF directed migration of BM-MSCs mainly to the anode. Directional migration occurred at a low thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
118
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 62 publications
(70 reference statements)
8
118
0
Order By: Relevance
“…SFRP1 expression in DFSC was not altered when DFSC were co-cultured with various ratios of DPSC, indicating that DFSC retain their potential to form periodontal tissues in the presence of DPSC. Recent studies have shown that ADAM28 overexpression has opposite effects on DPSC and DFSC: ADAM28 promotes proliferation of DFSC , while it inhibits proliferation and induces differentiation of DPSC (Zhao et al, 2011b). In co-cultures, ADAM28 expression was increased dramatically in both DFSC and DPSC, indicating that the proliferative potential resides within DFSC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…SFRP1 expression in DFSC was not altered when DFSC were co-cultured with various ratios of DPSC, indicating that DFSC retain their potential to form periodontal tissues in the presence of DPSC. Recent studies have shown that ADAM28 overexpression has opposite effects on DPSC and DFSC: ADAM28 promotes proliferation of DFSC , while it inhibits proliferation and induces differentiation of DPSC (Zhao et al, 2011b). In co-cultures, ADAM28 expression was increased dramatically in both DFSC and DPSC, indicating that the proliferative potential resides within DFSC.…”
Section: Discussionmentioning
confidence: 98%
“…DPSC and DFSC motion was tortuous, probably due to the frequent reversals in directions caused by successive protrusions with opposing orientations. Reduction of direction reversals makes cell movement less tortuous and cells adopt an oriented trajectory towards a chemical or electric signal (Aman and Piotrowski, 2010;Arocena et al, 2010;Zhao et al, 2011a). Indeed, the co-culture of DPSC and DFSC stimulated their migration abilities, particularly when these two stem cell populations were seeded in equal cell numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies and animal experiments have suggested enhancement of ossification by electrical stimulation [1,7,11,26,32,36,40]. In order to elucidate the mechanisms of electric-field stimulation on osteoprogenitor cells, many in vitro studies have applied direct electrical currents [8,12,29,37,41], capacitive coupling of electric fields [16,28,42] and inductive coupling of electric fields [9,19]. Ochi et al showed that the bone contact ratio around a dental implant inserted in the rabbit femur was almost 70% when capacitive coupling of electric fields (60 kHz, 10 Vp-p, sine wave signals) was applied for 8 hr/day over 14 days [32].…”
Section: Discussionmentioning
confidence: 99%
“…With a mechanical barrier, in this case collagen resorbable membrane, we prevent fibroblasts and other soft tissue cells to prematurely in grow into the bone defect area, since it is known that cells with osteogenic potential migrate more slowly [10]. Allogeneic platelet gel, which represents a source of growth factor, was proven to be just as efficient and safe to use as autologous for the regeneration of defects of long bones [8,11].…”
Section: Principles Of Tissue Guided Regeneration and Its Use In Surgerymentioning
confidence: 99%
“…Out of heterologous material, the most investigated is bovine, but also porcine bone grafts are in use. The aim of tissue engineering is to provide better materials and its efficiency with less side effects [14,15] The essential idea of this therapy was to combine the healing capacities of platelet-derived growth factors and osteogenic stem cells and the modeling capacity of the gel [3,6,10,14] …”
Section: Principles Of Tissue Guided Regeneration and Its Use In Surgerymentioning
confidence: 99%